Pasti in izzivi političnega in diplomatskega diskurza - Gorenc, Nina (Teorija in praksa, 2011)
Diplomacy is communication and language as the main means of communication is not only a vehicle for the transportation of ideas, but their active creator as well. The article aims to present special features which distinguish diplomatic discourse from political discourse and the problems faced by diplomats who are native speakers of minor languages. They are forced to express themselves in a foreign language or rely on the use of interpreters, which can lead to the distortion of meaning and related problems. Public diplomacy, as a response of diplomacy to media development, will be presented in the conclusion. Diplomacy is closely linked with negotiations, which are focused on the achievement of a compromise solution. Diplomats should be aware of that and thus employ such language which allows a compromise and can satisfy as many interests as possible. Language can thus reduce the explosive potential which could eventually lead to conflicts, create distance between parties and prepare them to adjust their positions. The opposite can be achieved by employing colourful language, rich in suggestive metaphors, which increases the danger of conflicts through the increased complexity of relations among parties. The prime function of diplomacy is to regulate conflicts and diplomats should not resort to the use of suggestive metaphors, historical analogies and emotional discourse; quite the opposite, they should employ less explicit and more neutral language so as not to increase the gap between negotiators (Russet and Starr, 1996).
Keywords: Diplomacija; Diplomacy; Komuniciranje; Communication; Discourse; Diskurz; Jezik in jeziki; Language and languages; diplomatski odnosi